Arrhythmias in children with a single ventricle - I. V. Plotnikova; O. Yu. Dzhaffarova; L. I. Svintsova; V. V. Saushkin; I. A. Kovalev (Бюллетень сибирской медицины, 2018)
Aim. The paper presents prevalence and disturbances of cardiac rhythm and conduction in children with a single ventricle (SV) at different stages of hemodynamic defect correction. It also analyzes risk factors of arrhythmia.Materials and methods. A total of 70 patients with SV was performed all stages of hemodynamic correction of defect. To assess disorders of rhythm and conduction, echocardiography, pulseoxymetry, cardiac catheterization, pulmonary angiography, ECG, and Holter monitoring were performed before and after surgery on all children at every stage of hemodynamic correction.Results. Absence of heart rhythm disturbances (HRD) at 1st stage of hemodynamic correction was 98.1%, at 2nd – 80%, at 3rd – 48.6% and at 4th – 41.5%. Sinus node dysfunction is the most often HRD from the second stage of hemodynamic correction. Statistical analysis showed significant decrease of saturation ((73 ± 12) и (81 ± 4)% correspondingly, p < 0.05) and increase of average pressure in the pulmonary artery after TCPC ((9.6 ± 4.2) and (11.5 ± 5.8)% correspondingly, p < 0.05) in children with heart rhythm disturbances in comparison to children without arrhythmias. The average age of children with arrhythmias after TCPC and after fenestration closure, correspondingly, was significantly higher than in the group of children without arrhythmias ((72 ± 43) mon and (52 ± 27) mon correspondingly, p < 0.05). Studies of arrhythmias in children with SV require follow-up as they significantly influence on the disease and life quality.